Use of Social Media for Scholarly Communication - Nurul Fikriati Ayu Hapsari; Iwin Ardyawin; Rohana; Dodi Firdausi Nuzula; Hasnah Hashim (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: Social media is widely used in the current educational context and significantly affects scholarly communication. This informal scientific communication activity is an activity that is not